Plant Antibacterial Activity Herb Klate (Hyptis Suaveolens) Against Bacteria Escherichia coli and Staphylococcus Aureus - Hure, Yuliana Evarista Dua; Moi, Maria Yasinta Moi; Ernaningsih, Dian Ernaningsih (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2023)
Hyptis suaveolens can be used as a traditional medicine for various diseases and as a natural pesticide to eradicate pests and diseases in plants. This study aims to determine the extract of the Hyptis suaveolens plant on the growth of E. coli and S. aureus bacteria and to determine the phytochemical profile qualitatively. The method used is the qualitative test method. Antibacterial activity testing was carried out using the agar diffusion method. With concentrations (10, 30, 50 and 100) %, positive control for Chloramphenicol and negative control for Dimethyl Sulfoxide. The phytochemical profile qualitative test methods include color change, precipitate and emulsion formation. The results showed the formation of the diameter of the inhibition zone. Inhibition of the growth of the test bacteria was indicated by the formation of the diameter of the inhibition zone around the paper disc. The diameter of the inhibition zone produced by E. coli bacteria at a concentration of 100% was 7.20 mm, a concentration of 50% was 6.40 mm and at a concentration of 30 and 10% there was no inhibition zone. In S. aureus bacteria characterized by an inhibition zone at 100% concentration of 7.90 mm, 50% concentration of 6.60 mm, 30% concentration of 6.35 mm, and 10% concentration of 6.20 mm. The positive control for E. coli bacteria was 13.16 mm and for S. aureus bacteria was 25.40 mm while the negative control did not have an inhibition zone. Hyptis suaveolens leaf herbal extract has more effect on S. aureus bacteria than E. coli bacteria. This is presumably due to differences in the components of the bacterial cell walls of S. aureus and E. coli. The cell wall of S. aureus bacteria contains lower lipid than E. coli bacteria. Based on the results of the study, the higher the concentration, the greater the inhibition zone formed, while the results of the phytochemical profile test showed that Hyptis suaveolens extract was thought to contain flavonoids, saponins and tannins which act as antibacterial compounds